15 May - Update on COVID-19 by David Nabarro - Nabarro, D. (International Livestock Research Institute, 2020)
This "beastly virus" nonetheless delivers an "opportunity that many of us believe was there waiting for humanity to demonstrate its strength," said Dr David Nabarro, special envoy to the WHO Director General Dr Tedros Adhanom Ghebreyesus on COVID-19, in a spirited and defiantly hopeful presentation at an online town hall of the International Livestock Research Institute (ILRI) town hall meeting on 15 May 2020.